Perancangan Sistem Informasi Peminjaman Alat Berbasis Web pada Mapala Se-Kota Malang - Sigit Teguh Prakoso; Sugeng Widodo; Yekti Asmoro Kanthi (J-INTECH ( Journal of Information and Technology), 2020)
Mapala (Mahasiswa Pecinta Alam) is a talent interest organization with outdoor activities. When going to do Mapala activities often lending equipment between Mapala organizations. Mapala organization has various activities such as mountain climbing, rock climbing, cave caving, and rafting. Each of these activities requires supporting equipment. Every natural activity, Mapala Organization often lends equipment in every existing Mapala Organization, related to equipment owned by every Mapala Organization in Malang City is incomplete and different. Related to Mapala it is necessary to have an information system to facilitate the process of borrowing equipment, in order to facilitate the borrowing of equipment and facilitate the recording of loan transactions. To fulfill the above needs, it is necessary to design a loan information system. This loan system is made using the PHP programming language through the CodeIgniter framework, and also MySQL which is used as a storage database. Facilities in this system include processing member data, lending transactions and replacements.